AZIN1-dependent polyamine synthesis accelerates tumor cell cycle progression and impairs effector T-cell function in osteosarcoma - Jiaming Yu; Chuanxia Zhang; Qinkai Zhang; Bing Lu; Guohao Lu; Chunxiao Zhang; Ru Qiu; Xinyue Wang; Changye Zou; Junjun Chu; Haizhou Li; Wei Zhao (Cell Death and Disease)
Abstract Osteosarcoma, the most prevalent malignant bone tumor among adolescents, frequently exhibits limited responsiveness to immunotherapy, a challenge attributed to poorly understood underlying mechanisms. Here, we identify enhanced polyamine biosynthesis as a key driver of osteosarcoma progression and immunotherapy resistance. We show that osteosarcoma cell proliferation and tumor growth rely on polyamine availability and that disruption of polyamine synthesis significantly boosts the cytotoxic efficacy of TCR-engineered T cells against osteosarcoma cells. Mechanistically, we reveal that the knockdown of antizyme inhibitor 1 (AZIN1) or suppression of polyamine production reduces MYC expression, leading to diminished tumor cell viability via the downregulation of cell cycle-related genes. Furthermore, reduced MYC levels are associated with changes in the expression of immunomodulatory cytokines and human leukocyte antigen molecules, pointing to a potential link with enhanced T-cell-mediated cytotoxicity. Collectively, our findings establish a pivotal role for the AZIN1-polyamine axis in osteosarcoma proliferation and immune evasion, and support the development of novel immunotherapeutic strategies targeting polyamine biosynthesis to combat this aggressive cancer.